Skenario Perubahan Penggunaan Lahan Pada Daerah Aliran Sungai Rongkong Tahun 2031 - Abkar; Arsyad, Usman; Barkey, Roland A (Fakultas Kehutanan, Universitas Hasanuddin, 2024)
This research aims to project changes in land use/cover (LULC) in 2031. The purpose of this research is to produce a land use database that is useful for watershed management planning that supports the quality and sustainability of the watershed. This research was conducted in the Rongkong watershed which includes two administrative areas, that is Luwu Regency and North Luwu Regency, which was carried out for four months through two stages, that is survey and data analysis. This study uses land use projections in 2031 using the Celular Automata–Markov modeling (CA-Markov). The results showed that there were 14 land use/cover classes in the Rongkong watershed with an interpretation accuracy of 89.21%, consisting of primary dry land forest, secondary dry land forest, secondary mangrove forest, settlements, plantations, dry land agriculture, mixed dry land agriculture, grasslands, shrubs, swamp scrub, ponds, open land and bodies of water. The projection of land use/cover in 2031 is in accordance with the results of observations of 87.40% in detail resolution and 88.70% in aggregate resolution, both in terms of area and spatial distribution. The projection results show that the highest area increase occurs in the plantation class of 6,694.18 Ha (142.56%), while the highest decrease in area occurs in the primary dry land forest class of 3,378.86 Ha (30.77%). Changes in land use/coverage can have an impact on environmental damage such as erosion and flooding, so it is necessary to take control measures in the form of land use directives to maintain the sustainability of the Rongkong watershed function.